Karta si︠e︡vernago Ledovitago okeana otʺ ustʹi︠a︡ ri︠e︡ki I︠A︡ny do Beringova proliva / Sostavlena s Russkikhʺ opiseĭ 1821-1825 godovʺ izdana Gidrografīcheskimʺ Departamentomʺ Morskago Ministerstva vʺ 1874 godu - Russia. Gidrograficheskīĭ departament (Sankt-Peterburg : Morskoe ministerstvo, Gidrograficheskīĭ departament; [Санкт-Петербург] : Морское министерство, Гидрографическій департамент, 1874)
Relief shown by form lines. Depths shown by soundings and isolines.; Title translation: Map of the Arctic Ocean from the mouth of the Yana River to the Bering Strait.; Greenwich and Pulkovo meridians given.; "Masshtab: 1/2,700,000 ili 50 versti︠e︡ v 1 angl. di︠u︡ĭmi︠e︡." = Scale 1/2,700,000 or 50 versts in 1 Engl. inch.; "No. 230" -- bottom right margin Grayscale; 1:2,700,000